PERLINDUNGAN HUKUM PEMEGANG POLIS PASCA PENGURANGAN NILAI MANFAAT PADA RESTRUKTURISASI PT. ASURANSI JIWASRAYA - Imam Maulana; Purwanto, Amsari Damanik (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
PT. Jiwasraya Insurance is one of the State-Owned Enterprises that determines the restructuring policy as a result of the company's insolvent condition. However, in the implementation process, several legal rules and principles were violated. This gives rise to several legal consequences and uncertainty regarding the policy holder's rights to the benefit value reduced in the initial insurance agreement, especially annuity insurance policies. This research uses a doctrinal approach. Based on this type of approach, this research is directed at a set of written norms/regulations and supporting literature materials. The results obtained in this research are after reducing the value of insurance benefits during the restructuring of PT. Jiwasraya Insurance has several legal consequences that are detrimental to policy holders and are not in accordance with statutory regulations. Apart from that, legal protection for policy holders is still not fully realized, so as a repressive effort to protect the rights of policy holders it is necessary to provide compensation or compensation which is also in accordance with legal theory and applicable regulations.